A General Evaluation on Current Global Threat of Coronavirus (Covid-19) Immuno Responsibilities - Beyaz, Seda; Gök, Özlem; Aslan, Abdullah (My University, 2022)
Covid-19 SARS-CoV-2 (severe acute respiratory syndrome-coronavirus-2) is a new type of coronavirus known as an infectious upper respiratory tract infection disease. The coronavirus, which poses a great threat to human health worldwide, emerged in Wuhan, China in December 2019. The most important reason for coronavirus epidemics to become a pandemic that the disease was easily transmitted by droplets in close proximity with infected people. The disease spread rapidly all over the world within a few months and it was declared a worldwide epidemic by the World Health Organization in March 2020. It poses a risk for severe diseases such as hypertension, diabetes, cardiovascular disease, cancer, chronic lung disease and chronic kidney disease in the advanced age group. Considering the mortality rates to date, great efforts have been made both worldwide and in our country to manifacture successful drugs and vaccines against Covid-19 infection. The main purpose of this review is to assist in an immune response and preventive work for Covid-19, thanks to the available information about the coronavirus epidemic that deeply affects humanity and the diseases it causes.
Keywords: Covid-19; Coronavirus; Spike protein; ACE2 reseptor; Treatment vaccine